Effectiveness of Trellis Model and Propagation Direction in Optimizing Growth and Yield of Long Bean Plants (Vigna sinensis L) - Fajriani, Sisca; Rahmawan, Dzahabika Setya; Ariffin, Ariffin (CV. Komunitas Dunia Peternakan, 2025)
The research aims to study the effect of a combination of the trellis model and the direction of plant propagation on the growth and yield of long beans. The environmental design used a randomized block design with six treatments, repeated 5 times. The treatment are the trellis models (fence, triangle and para-para) and plant propagation directions (vertical and mixed). Growth variables include plant length, number of leaves, leaf area, and net assimilation rate. Yield variables include pod length, number of pods, pod weight, and yield per hectare. The results of the research showed that the treatment of different models of trellis and the direction of propagation of long bean plants in the mixed propagation direction resulted in higher plant length, leaf area, net assimilation rate, pod length per plant, pod weight per plant and yield per hectare compared to the vertical propagation direction with the model. the same trellis. The para-para trellis model treatment with mixed propagation directions produced a pod length and number of pods per plant of 60.76 cm and 57.59 pods per plant, 19.30% and 14.31% higher than the para-para trellis model with vertical propagation direction. 58.29 cm and 56.05 pods. The treatment of para-para trellis model with mixed creeping directions produced pod weight per plant and yield per hectare of 1.64 kg per plant and 7.3 ton.ha-1, which was 15.49% and 15.37% higher than the para-para trellis model with vertical propagation direction, which produces 1.42 kg per plant and 6.70 tons ha-1.